Flood Modelling of Adyar Basin - D. Thiyagarajan., Mr; Vasanthakumar, V; Mohan Prabhu., K; Thamizhselvan., R (International Journal of Engineering and Technology, 2018)
This paper is about the flood modelling of Adyar basin which was done by integrating ArcGIS and HEC-RAS modelling software. The SRTM DEM of 30m resolution were used as base data in ArcGIS. The river banks, center line of the river and its boundary were processed in the HECGEO-RAS then this geometry data is exported for the further working process in the HEC-RAS. The data is imported in it then it is processed with the peak discharge values for the steady flow analysis. The data from HEC-RAS is again post processed in the ArcGIS for the creation of the inundation map for the Adyar River. The Flood model setup is created for the Adyar River. The current study will help to evaluate the extent of flood plain in the study area it also helps the administration to figure out height of the flood if it happens again in that particular area.Â Â